2021
DOI: 10.1177/1971400920987357
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic stroke as an initial presentation in patients with COVID-19: evaluation of a case series in an emergency in Brazil

Abstract: The disease caused by the new coronavirus, initially described in China in December 2019, became known as coronavirus disease 2019 and quickly spread to countries on all continents, becoming a pandemic with an important global impact. Despite being a virus that typically affects the respiratory tract, some studies have already described neurological manifestations associated with this infection, including acute ischaemic vascular insult. We report a case series including 30 patients, who presented with neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Also, patients admitted to the hospital with neurological symptoms without symptoms of COVID-19 may be diagnosed with COVID-19 in the tests performed. [18][19][20][21][22] In our study, it was observed that the majority of COVID-19-positive stroke patients were admitted to the hospital due to stroke and were diagnosed with COVID-19 through subsequent tests.…”
Section: Discussionmentioning
confidence: 70%
“…Also, patients admitted to the hospital with neurological symptoms without symptoms of COVID-19 may be diagnosed with COVID-19 in the tests performed. [18][19][20][21][22] In our study, it was observed that the majority of COVID-19-positive stroke patients were admitted to the hospital due to stroke and were diagnosed with COVID-19 through subsequent tests.…”
Section: Discussionmentioning
confidence: 70%
“…The extent to which pre-existing chronic liver conditions affect COVID-19 related complications remains to be elucidated. Smell and taste sensations as well as increased incidence of ischemic stroke have been observed in individuals with COVID-19 [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which pre-existing chronic liver conditions affect COVID-19 related complications remains to be elucidated. Smell and taste sensations as well as increased incidence of ischemic stroke have been observed in individuals with COVID-19 [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%